2012
DOI: 10.1186/1471-2458-12-423
|View full text |Cite
|
Sign up to set email alerts
|

A multi-component stair climbing promotional campaign targeting calorific expenditure for worksites; a quasi-experimental study testing effects on behaviour, attitude and intention

Abstract: BackgroundAccumulation of lifestyle physical activity is a current aim of health promotion, with increased stair climbing one public health target. While the workplace provides an opportunity for regular stair climbing, evidence for effectiveness of point-of-choice interventions is equivocal. This paper reports a new approach to worksite interventions, aimed at changing attitudes and, hence, behaviour.MethodsPre-testing of calorific expenditure messages used structured interviews with members of the public (n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
56
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(58 citation statements)
references
References 26 publications
2
56
0
Order By: Relevance
“…In addition, average stair climbing in the control building was 19.0% higher than in the intervention building and this site displayed no difference between stair climbing and descent. In a similar study by Eves, Webb, Griffin & Chambers [24], results showed significantly higher increase in stair climbing, when using two simultaneous interventions, rather than a single intervention. The two interventions were placed at the point of choice and inside the stairwell, similar to the intervention placements in the present study.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…In addition, average stair climbing in the control building was 19.0% higher than in the intervention building and this site displayed no difference between stair climbing and descent. In a similar study by Eves, Webb, Griffin & Chambers [24], results showed significantly higher increase in stair climbing, when using two simultaneous interventions, rather than a single intervention. The two interventions were placed at the point of choice and inside the stairwell, similar to the intervention placements in the present study.…”
Section: Discussionmentioning
confidence: 87%
“…Because of its current use in Norway, and lack of positive evidence, it is in need of re-testing. Previous research gives reasonable expectations towards a greater effect when combining interventions [24], and the combination of footprints and positive feedback has, to our knowledge, never been tested. All aforementioned interventions are created to influence decision making, while people retain their opportunity to choose freely.…”
Section: Introductionmentioning
confidence: 88%
“…Interventions with point-of-choice prompts at worksites increase stair use by only +0.1% on average 10) . However, in the present study, the average rate of stair use during the long-term campaign period was maintained above 51% in women and 60% in men.…”
Section: Discussionmentioning
confidence: 99%
“…We used message banners as point-of-choice prompts in our study. Such messages convince workers to change their behavior and can alter attitudes 10) . Point-of-choice prompts help translate positive intentions into behavior.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation